IDENTIFICATION OF FACTORS AFFECTING THE IMPLEMENTATION OF ELEMENTS OF RELEASE WITH NO EYE CONTACT IN RHYTHMIC GYMNASTICS IN ATHLETES OF THE CITY OF FORTRESS/CE (Fiep Bulletin - online, 2014)
The Rhythmic Gymnastics, or GR, as it is popularly known, is a sport that develops beauty, and athleticism. The most difficult elements of the sport, and they most value series are the "elements of risk." These elements are the following phases: launching device, spins down the device and retrieving the device. Therefore the objective of this study was to identify the main problems identified by the gymnasts in relation to risks. The methodology was performed exploratory field research with quantitative approach. The sample was composed of 60 athletes aged between 12 and 15 years of age. The instrument used was a questionnaire consisting of 11 questions (5 and 6 were objective questions were mixed - with objective justification). Among the results, the following were most prominent: 75 % of the gymnasts consider committing fewer errors when running the "risk elements" at the end of the year, 15 % at baseline and 10 % in half. Regarding the apparatus considered more difficult, 55 % responded clubs, 30 % tape, 10 % and 5 % ball rope. The unit arc was not cited. 55 % of the gymnasts reported feeling difficulty in implementing elements without visual control and 45 % responded that they have difficulties in these elements. As external factors that could disrupt 45 % of the participants pointed out the noise, bright lights, 25 %, 17% the presence of rivals and 13 % the presence of arbitration. On Thursday 70 % reported performing best elements of launching without the visual control during training and competitions in 22 %, 8% said there was no difference between training and competition. We conclude that to reach high performance, athletes can clearly see the advantages and difficulties while performing the "risks". However, it is still necessary to establish a method for effectively obtaining a technical improvement in the performance of these elements.
Keywords: Rhythmic Gymnastics; risk elements; training